Crafting Coherence from Complex Policy Messages: Educators' Perceptions of Special Education and Standards-Based Accountability Policies - Jennifer Lin Russell; Laura E. Bray (Arizona State University, 2013)
Federal special education and accountability policies requires that educators individualize instruction for students with disabilities, while simultaneously ensuring that the vast majority of these students meet age-based grade-level standards and assessment targets. In this paper, we examine this dynamic interplay between policies through analysis of policy documents and interviews that reveal how a sample of educators grapple with their simultaneous implementation. We found that educators made sense of some facets of the policies as complementary and others as contradictory. NCLB and IDEA offered consistent and specific guidelines defining "highly qualified" teachers and educators reported a clear and accurate understanding of these policy demands. On an issue where there was no specific guidance from NCLB-the placement of special education students-educators interpreted the law as promoting the inclusion of more students in general education courses, often to an extent that contradicted the guidance offered by IDEA. With respect to fundamental issues of teaching and learning, NCLB and IDEA represent contradictory theories of action and educators perceived conflict and expressed concerns about unintended consequences for students. Based on our empirical findings, we conclude with a set of theoretical propositions regarding how the alignment of policy messages influences educators' interpretation of policies, which in turn may have implications for how they enact policies.